Correspondence Effects with Torches: Grasping Affordance or Visual Feature Asymmetry?. Issue 4 (April 2014) - Song, Xiaolei; Chen, Jing; Proctor, Robert W.
Three experiments were conducted to determine whether an object-based correspondence effect for torch (flashlight) stimuli reported by Pellicano et al. [(2010). Simon-like and functional affordance effects with tools: The effects of object perceptual discrimination and object action state. Quarterly Journal of Experimental Psychology, 63, 2190–2201] is due to a grasping affordance provided by the handle or asymmetry of feature markings on the torch. In Experiment 1 the stimuli were the same as those from Pellicano et al.'s Experiment 2, whereas in Experiments 2 and 3 the stimuli were modified versions with the graspable handle removed. Participants in all experiments performed upright/inverted orientation judgements on the torch stimuli. The results of Experiment 1 replicated those of Pellicano et al.: A small but significant object-based correspondence effect was evident, mainly when the torch was in an active state. With the handle of the torch removed in Experiment 2, making the barrel markings more asymmetric in the display, the correspondence effect was larger. Experiment 3 directly demonstrated an effect of barrel-marking asymmetry on the correspondence effect: When only the half of the markings nearest the light end of the torch was included, the correspondence effect reversed to favour the light end. The results are in agreement with a visual feature-asymmetry account and are difficult to reconcile with a grasping-affordance account.